Perbandingan Pendapatan Umk Penerima Kredit Bakulan Dari BPR Sarimadu - Askitarizki Nasution; Djaimi Bakce (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This study aims to Analyze changed income before and after credit “bakulan” received by micro business in the BPR Sarimadu in Pekanbaru and formulate policy implications that have been done to improve the disbursement in the BPR Sarimadu, in order to increase revenue micro business. The sampling method is purposive sampling. Micro business who became sample on this research is the trading businesses of vegetable and fruit. There are 302 debtors of credit “bakulan” in BPR Sarimadu. 22 of them are vegetable and fruit trading businesses and they are including into the micro bussines. The analysis used different test average, the results showed that t greater than t table. Ho is rejected and H1 is accepted so it is concluded that there is a real difference in the average income of the debtor by micro business after getting credit bakulan in the BPR Sarimadu. Stated that the provision of credit bakulan is very effective in order to increase revenue debtors micro business.   Keyword: income, credit “bakulan", comparassion income.